2014
DOI: 10.1074/jbc.m113.545582
|View full text |Cite
|
Sign up to set email alerts
|

Amigo Adhesion Protein Regulates Development of Neural Circuits in Zebrafish Brain

Abstract: Background: Amigos are transmembrane proteins suggested to mediate adhesive interactions of cells. Results: Down-regulation of Amigo protein expression or inhibition of its function results in defects of fiber pathway development and disturbed locomotor functions in zebrafish. Conclusion:The neural form of Amigo is required for construction of functional neural circuitries. Significance: Amigo is identified as a novel factor that regulates formation of neuronal connections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In addition, we tested if subtle developmental differences across the larvae could lead to differences in activity and radial index. Using larval size and amigo1 gene expression as known reporters of developmental changes during zebrafish development [ 14 , 15 ], we did not find any significant correlation between these reporters and the individual activity or radial index of the population at 7 dpf (Additional file 1 : Figure S3D, E; P > 0.05 for all the comparisons, using two-sided t -tests). Finally, we showed that activity and radial index can describe inter-individual variability not only during free-swimming behavior but also in response to stimuli like light flashes, mechanical perturbation, or being in a novel tank (“ Methods ”; Additional file 1 : Figure S3F).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, we tested if subtle developmental differences across the larvae could lead to differences in activity and radial index. Using larval size and amigo1 gene expression as known reporters of developmental changes during zebrafish development [ 14 , 15 ], we did not find any significant correlation between these reporters and the individual activity or radial index of the population at 7 dpf (Additional file 1 : Figure S3D, E; P > 0.05 for all the comparisons, using two-sided t -tests). Finally, we showed that activity and radial index can describe inter-individual variability not only during free-swimming behavior but also in response to stimuli like light flashes, mechanical perturbation, or being in a novel tank (“ Methods ”; Additional file 1 : Figure S3F).…”
Section: Resultsmentioning
confidence: 98%
“…The clustered localization of AMIGO-1 on the soma and proximal dendrites of adult brain neurons is interesting in light of the role of AMIGO-1 during development as an adhesion molecule involved in development of neuronal circuitry. Knockdown of AMIGO-1 expression in developing zebrafish impairs the formation of fasciculated fiber tracts and disturbs the development of dopaminergic circuits (Zhao et al, 2014 ). However there are no gross anatomical abnormalities in the brains of constitutive global AMIGO-1 KO mice (Peltola et al, 2016 ), or, as shown here, in Kv2 dKO mice, which also have greatly reduced levels of AMIGO-1 expression, particularly in the neuronal PM.…”
Section: Discussionmentioning
confidence: 99%
“…The AMIGO family with leucine-rich repeats is identified by ordered differential display, which reveals a novel sequence induced by amphoterin, the neurite-stimulating factor [121]. In addition, the role of AMIGO2 in neurovascular units has been demonstrated, such as neuronal development and neural circuit in zebrafish brain [122].…”
Section: Pi3k-akt Pathwaymentioning
confidence: 99%